Tackles and sidesteps - Herman Wasserman (Communicare)
Since the introduction of the first tabloid to the South African market in 2001, and seemingly increasing with each subsequent entrant into this burgeoning market, debates about their role, the reasons for their success, their potential, and their ethics (or the lack thereof) have been raging in the popular press. This debate seems to suggest, among other things, that the questions raised by the introduction of tabloids are of primary concern to producers and consumers of the media itself – in other words, that tabloids need to be dealt with within the domain of the popular press itself. In this paper I argue that while these debates are seemingly set on evaluating the tabloid media, they also reveal – and perhaps even more so – the dominant normative assumptions and professional ideologies in the mainstream media. In debating and rejecting the journalistic excesses of the tabloids, these debates served as a form of paradigm repair to restore the image of an occupation in trouble. The question to be investigated by looking at these debates is whether the widespread criticism of tabloids should be seen as part of journalistic ritual, namely the routine application of ethical guidelines and the performance of professional standards, or whether these debates went deeper to provide a structural critique of the South African media.